Structural Changes in Manufacturing Industry at Division Level – Serbia and New EU Member States - Savić, Ljubodrag; Bošković, Gorica; Mićić, Vladimir (Industrija, 2015)
Research in this paper is oriented towards structural changes at the division level of the manufacturing industry. The goal of the research is to point at the significance of the efficient structural reforms of Serbia’s manufacturing industry, more precisely to point at the size, intensity, speed and directions of the changes made in its structure. In the paper, the basic indicators of structural changes are used, namely the trend of the share of employment and the value added. The size of the changes is analyzed by the standard deviation and the dispersion of growth rates, whereas the intensity of changes is analyzed by the elasticity of the divisions’ growth rates. A correlation analysis is used to determine the directions and nature of the connectedness of structural changes between divisions, whereas the direction of changes is shown by the Spearman rank correlation coefficient of their growth rates. The Structural Change Indicator is used for researching the pace and patterns of structural changes. At the division level, by applying the comparison method, differences in the directions, speed and patterns of the structural changes of the Serbian manufacturing industry are analyzed against the new EU member states for which there are comparative data (Bulgaria, Romania, Hungary, the Czech Republic, Poland, Slovenia and Slovakia). The research results indicate that growth rates were higher in those divisions in which reforms were more comprehensive, faster, more intensive and efficiently fully implemented.